NASIHAT PENDIDIKAN ANAK PERSPEKTIF IMAM AL-GHAZALI KAJIAN KITAB AYYUHAL WALAD - Romaida, Romaida; Robi’ah, Robi’ah; Darwis, Muhajir (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
Today, the majority of students are still indifferent when given advice. This is contrary to the principles of Islamic teachings that require Muslims to be kind in accepting masihat. This study aims to find out educational advice for learners, the perspective of Imam Al-Ghazali in the translation of the book Ayyuhal Walad and its relevance to education today. This type of research is library research (Library Research) focuses on the study of character thoughts. The results showed that there are several pieces of advice in studying, namely, educational advice aimed at getting closer to Allah SWT, advice to establish a good relationship between teachers and students, advice on being good for students, advice on choosing educational material that is worth learning, advice on choosing educational methods. Imam Al-Ghazali's thoughts have relevance to education today, where students in studying should set the goal of studying which is to get closer to Allah SWT. And students need knowledge to be able to achieve these goals